2016
DOI: 10.1074/jbc.m116.740605
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of N-cadherin by Collagen I-activated Discoidin Domain Receptor 1 in Pancreatic Cancer Requires the Adaptor Molecule Shc1

Abstract: Pancreatic ductal adenocarcinomas are highly malignant cancers characterized by extensive invasion into surrounding tissues, metastasis to distant organs, and a limited response to therapy. A main feature of pancreatic ductal adenocarcinomas is desmoplasia, which leads to extensive deposition of collagen I. We have demonstrated that collagen I can induce epithelialmesenchymal transition (EMT) in pancreatic cancer cells. A hallmark of EMT is an increase in the expression of the mesenchymal cadherin N-cadherin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…In PANC-1 cells, 7rh inhibited DDR1-mediated signaling induced by soluble collagen (50 µg/ml) in a concentration-dependent manner (Figure 3a). At pharmacologically-relevant concentrations, 7rh inhibited activation of PYK2 and PEAK1, signaling proteins downstream of DDR1 (40). However, 7rh did not affect the activation of focal adhesion kinase (FAK), an effector that has not been previously associated with DDR1-induced signaling (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In PANC-1 cells, 7rh inhibited DDR1-mediated signaling induced by soluble collagen (50 µg/ml) in a concentration-dependent manner (Figure 3a). At pharmacologically-relevant concentrations, 7rh inhibited activation of PYK2 and PEAK1, signaling proteins downstream of DDR1 (40). However, 7rh did not affect the activation of focal adhesion kinase (FAK), an effector that has not been previously associated with DDR1-induced signaling (23).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 7rh-mediated inhibition of DDR1 in gastric cancer cells reduced tumorigenic characteristics in vitro and tumor growth in vivo . Finally, collagen signaling and DDR1 activity has been linked to epithelial plasticity (23,40). We found evidence that 7rh induced a more differentiated tumor cell phenotype, which is consistent with improved efficacy of standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cadherins are a family of calcium‐dependent glycoproteins, which responsible for Ca 2+ ‐dependent cell‐cell adhesions. Of the members of this family, N‐cadherin (neuronal cadherin or cadherin‐2), a transmembrane glycoprotein, which is normally expressed in neuroectodermal and mesenchymal‐derived tissues, plays crucial role in lots of processes, such as cell‐cell adhesion, embryogenesis, gastrulation, neurulation, migration and invasion . Today, N‐cadherin is regarded as a vital marker of EMT .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the prognostic role of N‐cadherin in tumours still remains controversially. Some studies suggested that expression of N‐cadherin was generally upregulated in prostate, breast cancer and urothelial tumours, and was associated with poorer clinical outcomes . In addition, the upregulation of N‐cadherin was significantly related with postoperative recurrence in hepatocellular carcinoma (HCC) patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation